2019
DOI: 10.1039/c9dt01800j
|View full text |Cite
|
Sign up to set email alerts
|

Dialing in on pharmacological features for a therapeutic antioxidant small molecule

Abstract: Incorporation of pyridol into 12-membered pyridinophanes results in exceptional metabolic stability, low-toxicity, and controlled metal binding suggesting good pharmacological potential.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
41
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 19 publications
(49 citation statements)
references
References 68 publications
8
41
0
Order By: Relevance
“…As previously observed, this ligand is observed in both enol and keto forms in solution (the ratio between the two is unknown). 6 The presence of the keto form lowers the formation constant of the iron complex because the non-bonding electron pair from the pyridine N-atom, which would be donated to the metal center, is incorporated as part of the delocalized seven-center eight-electron system. To further support this, the thermodynamic stability with iron(II) decreased as the EW character of the pyridine substitution increased, with the exception of L4 ( Table 2).…”
Section: Formation Constantsmentioning
confidence: 99%
See 1 more Smart Citation
“…As previously observed, this ligand is observed in both enol and keto forms in solution (the ratio between the two is unknown). 6 The presence of the keto form lowers the formation constant of the iron complex because the non-bonding electron pair from the pyridine N-atom, which would be donated to the metal center, is incorporated as part of the delocalized seven-center eight-electron system. To further support this, the thermodynamic stability with iron(II) decreased as the EW character of the pyridine substitution increased, with the exception of L4 ( Table 2).…”
Section: Formation Constantsmentioning
confidence: 99%
“…1) has conformational rigidity and decreased basicity compared to cyclen. 6 Therefore, the inclusion of pyridine provides an avenue through which thermodynamic properties and complexation kinetics can be modulated. [3][4][5]7 Congeners of pyclen have been widely studied to tune their properties and reactivity.…”
Section: Introductionmentioning
confidence: 99%
“…It was later in the spotlight for its ability to form metal complexes [6][7][8], but its wider success was achieved thanks to its utilisation as a scaffold for the preparation of new materials that have proven effective in a variety of applications. Indeed, L derivatives decorated with different hanging functionalities have been studied for several biomedical (MRI contrast agents [9][10][11][12], antiproliferative treatments [13][14][15][16], radiotherapy [17,18], enzyme mimicking [19,20] and antioxidant activity [21][22][23]), chemosensing [24][25][26][27] and catalytic [28][29][30][31][32][33] applications. Very recently, (MRI contrast agents [9][10][11][12], antiproliferative treatments [13][14][15][16], radiotherapy [17,18], enzyme mimicking [19,20] and antioxidant activity [21][22][23]), chemosensing [24][25]…”
Section: Introductionmentioning
confidence: 99%
“…Anion-π interactions were also found to play an important role in the formation of highly organised polyiodide complexes [44,45] and iodide based permutable organised frameworks (POF) [46] with a pyridinium-based ligand such as Stoddart's blue box (BB, cyclobis(paraquat-p-phenylene)). (MRI contrast agents [9][10][11][12], antiproliferative treatments [13][14][15][16], radiotherapy [17,18], enzyme mimicking [19,20] and antioxidant activity [21][22][23]), chemosensing [24][25][26][27] and catalytic [28][29][30][31][32][33] applications. Very recently, it has been shown that L and its N-trimethylated derivative are capable of stabilising iodine-dense three-dimensional networks that might be relevant for crystal engineering purposes and the design of solid-state conductors [34].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation